Ghrelin exerts a proliferative effect on a rat pituitary somatotroph cell line via the mitogen-activated protein kinase pathway. - Nanzer, A; Khalaf, S; Mozid, A; Fowkes, R; Patel, M; Burrin, J; Grossman, AB; Korbonits, M (2004)
OBJECTIVES: Ghrelin is a brain-gut peptide with GH-releasing and appetite-inducing activities and a widespread tissue distribution. Ghrelin is the endogenous ligand of the GH secretagogue receptor type 1a (GHS-R1a), and both ghrelin and the GHS-R1a are expressed in the pituitary. There are conflicting data regarding the effects of ghrelin on cell proliferation. A positive effect on proliferation and activation of the mitogen-activated protein kinase (MAPK) pathway has been found in hepatoma, adipose, cardiomyocyte and prostate cell lines. However, ghrelin has also been shown to have anti-proliferative effects on breast, lung and thyroid cell lines. We therefore examined the effect of ghrelin on the rat pituitary cell line GH3. METHODS: RT-PCR was used for the detection of GHS-R1a and pre-proghrelin mRNA expression in GH3 cells. The effect of ghrelin on cell proliferation was studied using [(3)H]thymidine incorporation; cell counting and the activation of the MAPK pathway were studied using immunoblotting and inhibitors of the extracellular signal-regulated kinase 1 and 2 (ERK 1/2), protein kinase C (PKC) and tyrosine phosphatase pathways. RESULTS: GHS-R1a and ghrelin mRNA expression were detected in GH3 cells. Ghrelin, at 10(-10) to 10(-6) M concentrations, significantly increased [(3)H]thymidine incorporation (at 10(-9) M, 183+/-13% (means+/-s.e.m.) compared with untreated controls), while 12-phorbol 13-myristate acetate (PMA) at 10(-7) M (used as a positive control) caused a 212+/-14% increase. A reproducible stimulatory effect of desoctanoyl ghrelin was also observed on [(3)H]thymidine incorporation (135+/-5%; P<0.01 at 10(-9) M compared with control), as well as on the cell count (control 6.8 x 10(4)+/-8.7 x 10(3) cells/ml vs desoctanoyl ghrelin (10(-9) M) 1.04 x 10(5)+/-7.5 x 10(3) cells/ml; P<0.01). Ghrelin caused a significant increase in phosphorylated ERK 1/2 in immunoblotting, while desoctanoyl ghrelin showed a smaller but also significant stimulatory effect. The positive effect of ghrelin and desoctanoyl ghrelin on [(3)H]thymidine incorporation was abolished by the MAPK kinase inhibitor U0126, the PKC inhibitor GF109203X and the tyrosine kinase inhibitor tyrphostin 23, suggesting that the ghrelin-induced cell proliferation of GH3 cells is mediated both via a PKC-MAPK-dependent pathway and via a tyrosine kinase-dependent pathway. This could also be clearly demonstrated by Western blot analysis, where a transient increase in ERK 1/2 phosphorylation by ghrelin was attenuated by all three inhibitors. CONCLUSION: We have shown a novel role for ghrelin in stimulating the proliferation of a somatotroph pituitary tumour cell line, suggesting that ERK activation is involved in mediating the effects of ghrelin on cell proliferation. Desoctanoyl ghrelin showed a similar effect. As ghrelin has been shown to be expressed in both normal and adenomatous pituitary tissue, locally produced ghrelin may play a role in pituitary tumorigenesis via an autocrine/paracrine pathway.